The self‐sputtered contribution to the lunar exosphere. Issue 9 (23rd September 2013) - Poppe, A. R.; Halekas, J. S.; Sarantos, M.; Delory, G. T.
Abstract : [1] The lunar exosphere is produced by a combination of processes including thermal desorption, micrometeoroid bombardment, internal gas release, photon‐stimulated desorption, and charged‐particle sputtering. Here we investigate an additional mechanism not previously considered for the Moon, namely the role that newly born ions from the exosphere itself play in sputtering additional neutrals from the lunar surface, known as self‐sputtering. Our calculations suggest that this process may sputter neutrals into the lunar exosphere at a rate equal to or greater than charged‐particle sputtering due to passage through the Earth's plasma sheet when spatially averaged over the lunar dayside, while locally, self‐sputtering may equal or exceed solar wind charged‐particle sputtering and micrometeoroid bombardment. We use known or modeled densities and distributions of exospheric neutrals, laboratory‐derived values for the photoionization rates and neutral sputtering yields, and knowledge of the ambient electromagnetic environment at the Moon to derive estimates of the self‐sputtered neutral flux. We present the spatial variation of the self‐sputtered neutral flux and discuss the implications thereof. Key Points: We calculate self-sputtering fluxes for the Moon's exosphere. Self‐sputtering is anisotropic due to the convection electric field. Self‐sputtering can locally exceed other exospheric sources.